Islamic Ecotheology in Education: Institutional Practice and Contestation at Ma’had Al-Zaytun - Munawar-Rachman, Budhy; Aminulloh, Ali; Nopasari, Dewi; Nisak, Khoirotun (Parahyangan Catholic University, 2026)
Scholars increasingly understand the global ecological crisis not merely as an environmental problem but as a civilizational crisis rooted in the relationship between humans, God, nature, and the social order. This article examines the implementation of ecotheology in Islamic education at Ma’had Al-Zaytun, Indramayu, West Java, by positioning it as a form of religious educational practice that seeks to respond to the ecological crisis through the integration of faith, scientific knowledge, and ecological responsibility. The study employs a qualitative approach, using field observations conducted on December 10–12, 2025, in-depth interviews, and document analysis. The findings show that ecotheology at Ma’had Al-Zaytun does not remain at the normative level; instead, the institution operationalizes it as lived theology through an interdisciplinary curriculum, sustainable agricultural practices, an environmentally friendly lifestyle culture, and the management of socio-ecological relations with surrounding communities. However, this implementation also faces structural challenges, cultural resistance, and theological controversies related to interpretive religious authority and institutional sustainability. This article argues that Ma’had Al-Zaytun can be understood as a socio-ecological laboratory where Islamic ecotheology undergoes practical experimentation while simultaneously attracting critical debate. This study contributes to the development of ecotheological scholarship in Indonesia by positioning the pesantren as a significant arena for the renewal of Islamic education that responds to the ecological crisis, while acknowledging the social and theological tensions that accompany such efforts.